Pengaruh Pemakaian Bahan Tambah Limbah Plastik Kemasan Air Mineral Terhadap Kuat Tekan Dan Kuat Tarik Belah Beton - Gandjar Pamuji; Nor Intang Setyo H; Aan Nurur Rahman (Jenderal Soedirman University, 2008)
This article present result of research of usage plastic waste tidiness of mineral water (liquefied polypropylene) upon which add with variation of plastic waste equal t o 5%; 10% and 15%, examination conducted at 7, 14, 28 and 56 day for the compression strength test and age 28 day for concrete split strain strength test. Test object made in the form of cylinder of the size diameter 15 cm and high 30 cm. This research is conducted at Concrete Technological Laboratory of C i vil Engineering Jenderal Soedirman University. Research result expected can give information concerning benefit of plastic waste, knowing how big influence of addition of plastic waste to compression strength and concrete split strain strength and data source to all researchers to use this waste.